Social Determinants of Rural Secondary School Students’ Choice of Agricultural Career and its Implication for Counseling Services: A Case of Delta State, Nigeria - Osita , Egbule Elizabeta (Asian Journal of Agriculture and Rural Development, 2020)
This study unveils the factors that influence rural secondary school students to choose agriculture as a career or course of study. Many of the students chose a career in medicine and engineering before agriculture. Most (57.89%) had no counseling experience with a Guidance Counselor, but 81.14% were engaged in agricultural child labour. 83.77% were exposed to agriculture programmes on audio-visual media and visit to commercial farms. The few (10.09%) chose agriculture as an opportunity for self-employment, interest, profitable and easy nature of agriculture as a course of study and parents’ preference, among others. The social attributes of the students such as age, parents education & occupation, wealth status of parents, sex, knowledge of the subject, aptitude for prerequisite subjects, contact with guidance/counselors, involvement in agricultural child labour, exposure to mass media and visit commercial farms influenced their choice of agriculture as career or course of study.